Radiographic and Functional Results following Subtalar Arthroereisis in Pediatric Flexible Flatfoot - Ruiz-Picazo, David (Adv Orthop, 2019)
INTRODUCTION: Flexible flatfoot (FFF) is one of the most common skeletal disorders in children. In symptomatic patients who do not respond to conservative measures, surgery may be an option. Subtalar arthroereisis consists of limiting excessive eversion of the subtalar joint through different types of implants. MATERIALS AND METHODS: We carried out a retrospective study of 16 patients (32 feet) intervened for FFF with a subtalar device (arthroereisis), across the period of 2008-2015 with a minimum follow-up period of one year. Pre- and postoperative measures of the Moreau-Costa-Bartani angle, dorsoplantar (DP) and lateral (L) talocalcaneal angle, talonavicular coverage angle, and naviculocuboid overlap were used to evaluate correction of the deformity. Two expert surgeons from the Pediatric Orthopedics Unit took separate measurements of these angles for subsequent analysis purposes and to obtain the interobserver correlation coefficient for quantitative variables. Pre- and postoperative differences in the measurement of angles were ascertained using Student's t-test for paired samples; and a functional evaluation of the patients intervened was carried out pre- and postoperatively by administering the parent version of the Oxford Ankle Foot Questionnaire for Children (OxAFQ-C) during a clinical interview. All statistical analyses were performed using the SPSS v. 19.0 program (SPSS, Chicago, IL), with values being deemed statistically significant at p<0.05. RESULTS: A breakdown of the study population showed 81.25% (13 patients) males and 18.75% (3 patients) females, with mean age of 9 years (7-11). The interobserver coefficient for quantitative variables displayed a very high degree of concordance (0.7-0.9), indicating that the validity of the measures was adequate. Pre- and postoperative analysis of differences in the measurement of angles was statistically significant (p<0.005). In terms of functional evaluation, the postoperative results were positive, with statistical significance for the “school and play”, “emotional”, and “footwear” domains of the OxAFQ-C scale and no differences in the “physical” domain. CONCLUSION: Subtalar arthroereisis is a valid option for the treatment of symptomatic pediatric flatfoot, with good postoperative functional and radiographic results.